Continuing Medical Education Questions: October 2018. (October 2018) - Ho, Edith Y.
Abstract : N/A: To receive CME/MOC credit for this activity, please go to: http://acgjournalcme.gi.org/ Article Title: Refocusing IBD Patient Management: Personalized, Proactive, and Patient‐Centered Care